2020
DOI: 10.3390/molecules25204753
|View full text |Cite
|
Sign up to set email alerts
|

Gut/Oral Bacteria Variability May Explain the High Efficacy of Green Tea in Rodent Tumor Inhibition and Its Absence in Humans

Abstract: Consumption of green tea (GT) and GT polyphenols has prevented a range of cancers in rodents but has had mixed results in humans. Human subjects who drank GT for weeks showed changes in oral microbiome. However, GT-induced changes in RNA in oral epithelium were subject-specific, suggesting GT-induced changes of the oral epithelium occurred but differed across individuals. In contrast, studies in rodents consuming GT polyphenols revealed obvious changes in epithelial gene expression. GT polyphenols are poorly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…The catechins act in a dual modality, stimulating healthy gut microbes and inhibiting the proliferation of Campylobacter jejuni, Bacillus cereus, Escherichia coli, Clostridium perfringens, Legionella pneumophila, and Helicobacter pylori through a disruption of the cell membrane. Furthermore, green-tea polyphenols are able to create an overproliferation of Faecalibacterium, Bifidobacterium, Eubacterium, and Roseburia that lead to an increase in SCFAs with proven effects against colorectal cancer because they suppress lipopolysaccharide synthesis and, consequently, potentiate immune system function and exert an anti-inflammatory action [76][77][78][79][80][81][82]. Citrus fruits, like Citrus reticulate, or mandarin oranges; Citrus sinesis, or sweet oranges; Citrus depressa, or flat lemons; Citrus aurantium, or bitter oranges; and, especially, Citrus tangerine, or tangerines, contain nobiletin, a flavone with a chemical structure of three aromatic rings, each one linked to specific molecular groups.…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The catechins act in a dual modality, stimulating healthy gut microbes and inhibiting the proliferation of Campylobacter jejuni, Bacillus cereus, Escherichia coli, Clostridium perfringens, Legionella pneumophila, and Helicobacter pylori through a disruption of the cell membrane. Furthermore, green-tea polyphenols are able to create an overproliferation of Faecalibacterium, Bifidobacterium, Eubacterium, and Roseburia that lead to an increase in SCFAs with proven effects against colorectal cancer because they suppress lipopolysaccharide synthesis and, consequently, potentiate immune system function and exert an anti-inflammatory action [76][77][78][79][80][81][82]. Citrus fruits, like Citrus reticulate, or mandarin oranges; Citrus sinesis, or sweet oranges; Citrus depressa, or flat lemons; Citrus aurantium, or bitter oranges; and, especially, Citrus tangerine, or tangerines, contain nobiletin, a flavone with a chemical structure of three aromatic rings, each one linked to specific molecular groups.…”
Section: Colon Cancermentioning
confidence: 99%
“…Experiments in a mouse model about an estrogen-receptor (ER) negative mammary tumor showed that polyphenols alone did not induce a significative change in the gut-microbiota composition of healthy mice, even if they reduced significantly the rate of Firmicutes communities; in contrast, after cancer onset, these natural compounds effectively modified gut microbes, leading to a reduction of Proteobacteria and an increase in Bacterioides, compared to the control group. Furthermore, these changes are more evident after a combined administration of both broccoli sprouts and green-tea polyphenols [76][77][78][79][80][81]. Other plants and vegetables have shown antioxidant and anticancer properties.…”
Section: Breast Cancermentioning
confidence: 99%
“…Green tea contains various types of polyphenols, commonly called green tea polyphenols (GTP), which include flavonoids (catechins), tannins, theaflavins, and phenolic acids [ 23 ]. Major GTPs include catechins (50–55%) like epicatechin (EC), epicatechin-3-gallate (ECG), epigallocatechin (EGC), epigallocatechin-3-gallate (EGCG), and phenolic acids like gallic acids [ 24 ]. GTP undergoes biotransformation and produces various bioactive metabolites including 4′-O-methyl-epigallocatechin (4′-MeEGC); EGCG-sulfate; EGC-sulfate, 5-(3,4′,5′-trihydroxyphenyl)-γ-valerolactone (valeric acid derivatives), and phenolic acids like gallic acid, coumaric acid, and caffeic acid (refer to Table 1 for more details) [ 25 ].…”
Section: Gastroprotective Activity Of Dietary Polyphenols and Their Bioactive Metabolites Through Modulating Gmmentioning
confidence: 99%
“…As aforementioned, catechins are the major ingredients of GTPs, of which EGCG is considered as the major catechin. EGCG possesses an array of biological activities including anti-inflammatory, anti-microbial, antioxidant, anti-platelet aggregation, anti-cancer as well as cardioprotective and neuroprotective properties [ 24 , 26 , 27 ]. Even though GTP (especially EGCG) possesses beneficial properties, its low bioavailability is one of the major issues due to its high water-solubility (unstable), and high sensitivity toward pH, temperature, and light.…”
Section: Gastroprotective Activity Of Dietary Polyphenols and Their Bioactive Metabolites Through Modulating Gmmentioning
confidence: 99%
“…Therefore, not only parent compounds (such as EGCG) have been associated with cancer protection but also their metabolites, which raises the question of how the microbial metabolization of polyphenols could affect cancer prevention. This question was raised by Adami et al [ 50 ], claiming that inter-individual variations in the microbial communities could lead to different responses against cancer. If a metabolite is an effective protector, people lacking the species in charge of producing it would potentially have less protection.…”
Section: Influence Of Green Tea On Health Via Gut Microbiotamentioning
confidence: 99%